2009
DOI: 10.2486/indhealth.47.589
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Occupational Health ―A Systematic Review

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of mortality and morbidity in industrialized countries 1) . In a working population, occupational factors are believed to pose a threat to workers' cardiovascular health. Substantial research has shown that adverse physical and psychosocial work environments and working conditions, such as shift work and excessive workload, are related to CVD. To examine the acute and chronic effects of such work-related factors on the cardiovascular system, cardiac a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 81 publications
3
127
1
5
Order By: Relevance
“…Heart rate variability (HRV) is a highly reliable predictor of cardiovascular diseases and is an assessment tool of heart function 5) . The adjustment of the autonomic nervous system (ANS) involves the balance of sympathetic and parasympathetic nerve activity and can represent changes in psychological status 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) is a highly reliable predictor of cardiovascular diseases and is an assessment tool of heart function 5) . The adjustment of the autonomic nervous system (ANS) involves the balance of sympathetic and parasympathetic nerve activity and can represent changes in psychological status 6) .…”
Section: Introductionmentioning
confidence: 99%
“…One field study has shown lower FMD among experienced shift workers (19). By contrast, HRV has been assessed more frequently in field studies of shift workers (20) with studies predominantly showing a shift in the sympathetic/parasympathetic balance. It is not known, however, what aspects of shift work are causative.…”
mentioning
confidence: 99%
“…We build upon this theory to compose XTL. We use the Integrated Workload Scale (IWS) [6] to measure subjective load and the extensively-researched heart rate variability (HRV) to identify physiological arousal due to workload change [7][8][9][10][11][12]. In the next sections, we elaborate these measures in more detail for the setting described above.…”
Section: Approachmentioning
confidence: 99%
“…HRV can be calculated in various ways roughly divided in time domain methods and frequency domain methods [11]. We use the most common occupational health method [12]: SDNN, the standard deviation (SD) of all normal-to-normal (NN) intervals, from the time domain and the low-high frequency (LF/HF) ratio in the frequency domain. We calculate both measures in the same 5 min base-slot used for the calculation of XTL and IWS.…”
Section: Heart Rate Variability (Hrv)mentioning
confidence: 99%
See 1 more Smart Citation